Evaluation of effectiveness of Mass Vaccination Campaign against Peste des petits ruminants in Chhattisgarh state, India. Issue 3 (28th March 2019) - Govindaraj, Gurrappa Naidu; Roy, Goutam; Mohanty, Barada Shankar; Balamurugan, Vinayagamurthy; Pandey, Arvind Kumar; Sharma, Varsha; Patel, Aparna; Mehra, Mausam; Pandey, S. K.; Roy, Parimal
Summary: The study evaluated the effectiveness of 'Mass Vaccination Campaign (MVC)' implemented against the contagious transboundary OIE notified Peste des petits ruminants (PPR) in sheep and goats on the lines of 'pulse polio campaign' for humans in Chhattisgarh state, India. The effectiveness was evaluated on the axes of adequacy, financial viability under with and without MVC through differencing under various scenarios and options and programme impact from a farmer's perspective. The adequacy evaluation revealed that the reported outbreaks, diagnosed and death cases declined under PPR‐MVC inconsonance with increased vaccination coverage. Furthermore, the seroconversion increased during post PPR‐MVC implies elevated immunity levels in the sheep and goat population. The estimated mean mortality loss was USD 45.2 and USD 16.5 per animal in goats and sheep, respectively, whereas the treatment and opportunity cost of labour was USD 1.9 and USD 2.5 per animal respectively. Under the low PPR incidence scenario, benefit: cost ratio, net present value and internal rate of return were 4.9:1, 48.9 million USD and 146.6%, whereas it was 12.4:1, 142.7 million USD and 430.4% and 13.5:1, 156.7 million USD and 430.4% under medium and high incidence scenarios. Furthermore, the option of vaccinating 100% risk population during the first year followed by 30% during subsequent years to cover naïve population will maximize benefits than 100% coverage every year; nevertheless, benefits outweighs cost manifolds in both of these options. The farmers had a positive opinion on the overall services provided under PPR‐MVC and the results provide the empirical evidence on effectiveness of 'mass vaccination' for its replication in other states of India or countries with similar socio‐economic and rearing environments.